Habituasi Pendidikan Karakter Siswa Sekolah Dasar untuk Mewujudkan Profil Pelajar Pancasila pada Paradigma Kurikulum Merdeka - Heryon B. Mbuik; Asti Y. Benu (Departement of Mathematics Education, 2024)
Research related to character education habituation to realize the Pancasila student profile in the Independent Curriculum paradigm at GMIT Kuanino 2 Elementary School, Kupang City was carried out with the aims of: 1) knowing and describing the implementation of the Independent Curriculum in the elementary learning process; 2) knowing and describing the actualization of Pancasila student profiles in learning; and 3) knowing and describing efforts to habituate elementary school students' character education to realize the Pancasila student profile in the Independent Curriculum paradigm. This type of research is qualitative research using a descriptive approach. The result of carrying out this research is that character education habituation for elementary school students to realize the Pancasila student profile in the Independent Curriculum paradigm is carried out through various strategies, including: 1) Integration in Learning: Integrating character values ​​in each subject. For example, in mathematics lessons, students are taught about honesty through activities related to measurements and calculations, 2) Extracurricular Activities: Organizing extracurricular activities that support character development, such as scouting, social activities, or art, which not only improve skills but also build cooperation and leadership; and 3) Teacher Example: The role of the teacher as a role model is very important. Teachers showing positive behavior and applying Pancasila values ​​in daily interactions have provided concrete examples for students.